The Comprehensive Systematic Review of Association of QT prolonging medications torsades de pointes in hospitalized patients - Fionny Novira Azelikha; Irma Winastuti Rosmanadewi (The International Journal of Medical Science and Health Research, 2025)
Introduction: Drug-induced QT interval prolongation and its progression to torsades de pointes (TdP), a potentially fatal polymorphic ventricular tachycardia, represent a significant clinical challenge in hospitalized patients. Numerous medications across various therapeutic classes possess this off-target adverse effect, creating a complex landscape for risk management, especially in vulnerable inpatient populations often burdened by comorbidities, polypharmacy, and acute illness. A comprehensive synthesis of the evidence regarding the incidence, risk factors, and mitigation strategies is crucial for optimizing patient safety. Methods: This systematic review was conducted by screening studies from multiple databases based on pre-defined criteria. The population of interest was hospitalized patients of any age receiving medications known to prolong the QT interval. The primary outcome was the occurrence of TdP, with clear diagnostic criteria required. Included study designs were observational studies, randomized controlled trials, systematic reviews, meta-analyses, or case series with ≥10 patients. Data extraction covered study population, specific QT-prolonging drugs, TdP outcomes, risk factors, QT monitoring methodologies, and key statistical findings (Tleyjeh et al., 2020; Vandael et al., 2017). Results: Analysis of 80 included studies revealed marked heterogeneity in TdP incidence across drug classes. Class III antiarrhythmics (e.g., dofetilide, ibutilide) demonstrated the highest risk (1-17%), directly related to their potassium channel-blocking mechanism (Mazur et al., 2001; Bianconi et al., 2000). Antimalarials (hydroxychloroquine/chloroquine), widely used during the COVID-19 pandemic, showed a TdP incidence of 0.06-0.72%, which increased when combined with azithromycin (Aleem et al., 2021; Diaz-Arocutipa et al., 2021). Other agents like fluoroquinolones, antipsychotics, and methadone were associated with lower absolute TdP risk (<0.1-1%) but significant QTc prolongation (Gorelik et al., 2018; Garcia et al., 2025; Lovell et al., 2018). Key patient-related risk factors included female sex, advanced age, baseline cardiac disease, electrolyte disturbances (hypokalemia, hypomagnesemia), and polypharmacy with multiple QT-prolonging drugs (Johnston et al., 2013; Vandael et al., 2017). Discussion: The disparity between high rates of QTc prolongation and low incidence of TdP highlights the poor positive predictive value of QT elongation alone for arrhythmic events. The translation from prolonged repolarization to TdP depends on additional factors such as increased repolarization heterogeneity (e.g., Tpeak-Tend interval), the presence of triggers (e.g., bradycardia, pauses), and individual genetic susceptibility (Strauss et al., 2017; Tse et al., 2018). Effective risk mitigation involves vigilant monitoring (using optimal correction formulas like Rautaharju's), maintaining normal electrolyte levels, employing clinical decision support systems, and considering protective interventions like magnesium administration for high-risk drugs like ibutilide (Patsilinakos et al., 2010; Othong et al., 2018). Conclusion: The risk of drug-induced TdP in hospitalized patients is highly variable and contingent on a multifactorial interplay between specific drug properties, patient susceptibility, and clinical context. While certain drug classes (Class III antiarrhythmics) necessitate stringent inpatient monitoring protocols, for many others, the absolute risk of TdP is low when prescribed judiciously with appropriate patient assessment and monitoring. A stratified, individualized approach to risk assessment and management, incorporating modifiable risk factors and systematic monitoring strategies, is essential to maximize therapeutic benefits while minimizing arrhythmic hazards.